“+CLICK”: pilot of a web-based training program to enhance ART adherence among HIV-positive youth. - Shegog, Ross; Markham, ChristineM.; Leonard, AmyD.; Bui, ThanhC.; Paul, MaryE. (AIDS Care, 2012)
Youth account for almost half of all new HIV infections in the United States. Adherence to antiretroviral treatment (ART) is critical for successful management, yet reported adherence rates for youth are often low. This study pilot-tested “+CLICK,” an innovative, web-based, adherence intervention for HIV-positive youth as an adjunct to traditional clinic-based, self-management education. The theory-based application, developed for HIV-infected youth, 13–24 years of age, provides tailored activities addressing attitudes, knowledge, skills, and self-efficacy related to ART adherence. HIV-positive youth (N=10) pilot-tested “+CLICK” to assess usability (ease of use, credibility, understandability, acceptability, motivation) and short-term psychosocial outcomes (importance and self-efficacy related to ART adherence) using a single-group, pre-/post-test study design in a hospital-based pediatric clinic (n=8) and home (n=2) location. Youth were mostly female (80%) and Black (80%). Mean age was 17.8 years (SD=2.65, range 14–22). All were infected perinatally and had been living with HIV all their lives. Most learned their HIV status by age 10 years. Sixty percent reported an undetectable viral load, whilst 10% reported a viral load of over 50,000. Half (50%) reported a normal CD4 count, whilst 20% reported having low CD4 (<200). Usability ratings indicated “+CLICK” was very easy to use (70%), trustworthy, and understandable (both>90%). Most (70%) indicated they would use “+CLICK” again. Short-term psychosocial outcomes indicate significant increase in medication adherence self-efficacy (p<0.05), perceived importance of taking antiretroviral medicine close to the right time every day (p<0.05), and knowledge about HIV and adherence (p<0.01). Other psychosocial variables and behavioral intentions were not significantly impacted. Results suggest that “+CLICK” has the potential to affect psychological antecedents to ART adherence. Further research on long-term and behavioral effects is indicated prior to broader dissemination into clinical practice.